Laser measurements of ion velocities in plasmas - Woodcock, B; Freegarde, T; Hancock, G (IEE, 1997)
The behavior of the dominant ground state N2+ ion in a RF plasma struck in molecular nitrogen is studied. Two types of experiments are carried out, with the beam either parallel or perpendicular to the driven electrode. In the first measurement, changing the height of the laser beam above the driven electrode gives information on the concentration dependence of the ions as a function of distance, h. The Doppler profile gives the ions' velocity components parallel to the electrode. For measurements perpendicular to the electrode, careful fluorescence imaging allows the determination of the perpendicular velocity components as a function of h, and the effect of the changing field on the velocity distribution through the sheath region can be explored.